2022
DOI: 10.1002/er.8021
|View full text |Cite
|
Sign up to set email alerts
|

The use of wood waste from construction and demolition to produce sustainable bioenergy—a bibliometric review of the literature

Abstract: Summary The purpose of this paper is to investigate the perspective of using wood waste, especially the one that resulted from the construction and demolition activities, to produce sustainable bioenergy. The context of this research is characterized by a more accelerated need for development, a growing need for energy to fuel all human activities, and a greater awareness of the pressure on the environment and the negative effects produced. One of the major challenges for environmental protection is the issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Interestingly, it was found that the conductivity of the mixture increases almost proportionally to the surface area of the Al 2 O 3 particles, which strongly implies that the interface is the source of the fast Li + -conduction. This finding led to the space charge model later established by Maier and co-workers, whose detailed discussion will be conducted in section .…”
Section: Composite Solid Electrolytesmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, it was found that the conductivity of the mixture increases almost proportionally to the surface area of the Al 2 O 3 particles, which strongly implies that the interface is the source of the fast Li + -conduction. This finding led to the space charge model later established by Maier and co-workers, whose detailed discussion will be conducted in section .…”
Section: Composite Solid Electrolytesmentioning
confidence: 92%
“…Correspondingly, the ionic conduction close to the interfacial core is also affected because of the modified concentration of charge carrying defects. Formally, the modified defect thermodynamics close to the interfaces in ionic conductors can be described by the space-charge model, which has been reviewed in several seminal works by Maier. ,, Briefly, the discontinuity at the interface leads to deviations from local electroneutrality and the formation of a narrow charged zone, i.e., the so-called “space-charge zone”, where the concentration of the charge carrying defects is modified and the conductivity is influenced correspondingly (Figure (a)).…”
Section: Conduction Mechanismsmentioning
confidence: 99%
“…For this study's bibliographic data analysis, Bibliomatrix ® was selected due to its rich features and reliable data visualization capabilities [39][40][41]. In the construction field, recent literature reviews have focused on topics such as BIM collaboration and risk [42], construction waste [43], wood waste from construction [44], and stakeholder relationships in off-site construction [45]. By using Bibliomatrix ® , researchers can conduct co-word analysis and co-citation network analysis to visualize the field's research evolution [46][47][48].…”
Section: Methodsmentioning
confidence: 99%
“…Buildings 2023, 13, x 4 of 26 have focused on topics such as BIM collaboration and risk [42], construction waste [43], wood waste from construction [44], and stakeholder relationships in off-site construction [45]. By using Bibliomatrix ® , researchers can conduct co-word analysis and co-citation network analysis to visualize the field's research evolution [46][47][48].…”
Section: Annual Publication and Main Sourcesmentioning
confidence: 99%
“…The rapid growth of construction and building waste is a by-product of rapid urbanization. Construction and building waste make up a considerable quantity of the total urban waste (Ding et al 2023), and it is disposed of randomly or buried without proper treatment, causing severe environmental issues like groundwater contamination and land resource occupation (Kabirifar et al 2020, Maier 2022). Recycling of construction and demolition waste(C&DW) varies from country to country and region to region.…”
Section: Introductionmentioning
confidence: 99%